Sanksi Adat Pete’an dalam Perspektif Hukum Islam - Rofi’ Al Muhlis (Institut Agama Islam Negeri (IAIN) Kediri, 2017)
In a law, there are customary laws which legalized by positive law and Islamic law. The culture communities in the District Ngadas Village Poncokusumo Malang, there is a costomary law that called “pete’an” that is pregnancy test for girls and widows aimed at preventing acts pregnant out of legal wedding. This custom is quite effective and bringing great results in the reduction and prevention acts pregnant out of legal wedding, so that the people and the leaders of Ngadas village support the implementation and preservation of the custom pete’an. The implementation of custom pete’an in the perspective of Islamic law conformable with nash and shara’. The customary sanctions that applicable in pete’an in the perspective of Islamic law is not in accordance with the penalties for sex-free and still a minor penalty. However, by looking at the number of cases is only 1-3 cases within 5-7 years after the implementation of this pete’an custom shows that a custom implementation of pete’an very effective in reducing and preventing unwedding act that begins with the act of free sex.